Time-restricted feeding of pigs: social and feeding behavior - J Vargas Vargas; J V Craig; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1984)
Twenty finishing pigs were used to evaluate effects of time-restricted feeding on social interactions and feeding patterns of pigs at feeding time. Correlation analysis for pairs of traits, involving feeding activities, social interactions, and rate of gain indicate that more aggressive pigs went first to the feeder, fed more frequently, and gained faster. Although on continuous artificial lighting, timed-fed pigs displayed more feeding and aggressive behavior during day light hours.; Swine Day, Manhattan, KS, November 15, 1984
Keywords: Swine day; 1984; Kansas Agricultural Experiment Station contribution; no. 85-132-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 461; Swine; Social behavior; Feeding behavior